Analisis Sistem Budi Daya Tanaman Talas (Colocasia esculenta L.) di Kelurahan Bubulak, Bogor Barat, Jawa Barat - Nur Habibah; I Wayan Astika (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Taro plant (Colocasia esculenta L.) is a food crop in the form of tubers with a high carbohydrate content and is one of the alternative and functional food ingredients in Indonesia. The purpose of this study is to describe the types of taro cultivation systems in Bubulak Village, Bogor, West Java, and identify the factors that influence the taro cultivation system. The method used in this research is a descriptive method with a qualitative approach, which is knowing and getting a picture of the kinds of taro cultivation systems in Bubulak Village. This study uses indicators of the cultivation system which includes cropping patterns, cultivation management, cultivation production results, cultivation constraints, and the sustainability of the taro cultivation system in Bubulak Village. Based on the results of the analysis, there are two kinds of taro cultivation systems in Bubulak Village, namely monoculture and polyculture. Polyculture taro cultivation system with intercropping is considered more appropriate and effective because it can increase land productivity and create ecological stability by decreasing pest and disease attacks. Keywords: Cultivation management, cultivation system, monoculture, polyculture, taro